PENGERTIAN, PRINSIP, CIRI-CIRI, DAN TUJUAN EKONOMI ISLAM MENURUT PARA AHLI - Sindi Oktavia Tri Rahayu; Fitria Ningih; Adinda Amelia; M.Yusuf Bahtiar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this research is to identify and gain a deeper understanding of the concept of Islamic economics, which includes the definition, principles, objectives, and characteristics of the Islamic economic system based on the views of experts. This study employs a qualitative research method. The type of research used is descriptive qualitative research, which is a form of research aimed at describing or illustrating existing phenomena, both natural phenomena and human-engineered phenomena. The research design used in this study is a literature review or library research. Islamic economics is an economic system based on Islamic values derived from the Qur’an and Hadith. Etymologically, the term economics comes from the word oikonomia, which means household management. However, from an Islamic perspective, the concept of economics is not only related to the management of resources to fulfill human needs but must also be grounded in moral values, ethics, and responsibility to Allah SWT.